2001
DOI: 10.2307/3061099
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Influences on Insect Emergence Production from Central Platte River Wetlands

Abstract: The physical template of freshwater ecosystems has a pervasive influence on biological communities and processes. To examine the influence of hydrology on wetland insect communities, we quantified insect emergence from five riparian sloughs in the central Platte River valley. Annual hydroperiods of the wetlands ranged from 94 to 365 d/yr, and frequency and magnitude of drying events were inversely proportional to hydroperiod length. Three emergence traps were placed in each wetland from April through November … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 30 publications
7
30
2
Order By: Relevance
“…Our estimates of emergent biomass for individual taxa were equal to, or exceeded, estimates for some aquatic insect communities in stream (Fisher and Likens 1973), wetland (Whiles and Goldowitz 2001), and pond systems (Naiman et al 1986). Our estimates for salamander assemblages were equal to emergent biomass of midges from open-water habitats of an Alabama wetland (0.5 g DM m À2 year À1 ; Stagliano et al 1998) and exceeded exports of final instar caddisflies migrating from a Nebraska wetland (0.3 g AFDM m À2 year À1 ; Whiles et al 1999).…”
Section: Energy Flow To Forestmentioning
confidence: 62%
See 1 more Smart Citation
“…Our estimates of emergent biomass for individual taxa were equal to, or exceeded, estimates for some aquatic insect communities in stream (Fisher and Likens 1973), wetland (Whiles and Goldowitz 2001), and pond systems (Naiman et al 1986). Our estimates for salamander assemblages were equal to emergent biomass of midges from open-water habitats of an Alabama wetland (0.5 g DM m À2 year À1 ; Stagliano et al 1998) and exceeded exports of final instar caddisflies migrating from a Nebraska wetland (0.3 g AFDM m À2 year À1 ; Whiles et al 1999).…”
Section: Energy Flow To Forestmentioning
confidence: 62%
“…We calculated total surface area as the product of transect interval length and the sum of transect wetted lengths; the lengths of transects where water was ‡0.3 m deep were summed to estimate surface area for deep-water habitats, and the difference between these values was littoral surface area (Masser and Jensen 1991). Surface areas of temporary ponds changed seasonally, so we constructed linear and quadratic regression models to predict surface area and the proportion of each habitat type from staff gauges installed in these ponds (Whiles and Goldowitz 2001). We used seasonal maximum perimeter (P) and surface area (A) to calculate P:A ratios for all ponds.…”
Section: Physical Habitatmentioning
confidence: 99%
“…Vaňhara (1986), in describing the effect of water management (drainage) on brachyceran composition at a wet-woodland in Moravia has noted, ''Of Sciomyzidae only 42% of species and 14.9 % of individuals remained, but a fundamental change took place in favour of species feeding on land snails'' (Vaňhara 1986). Also, a study of Diptera at temporarily flooded sloughs in North America indicated that sites with an intermediate hydroperiod (296 days = 81% of the year) were most species-rich and abundant, but that Sciomyzidae were prominent (in terms of abundance and production) at sloughs with hydroperiods between 96 (=26% of the year) and 158 (=43% of the year) days (Whiles and Goldowitz 2001). The results of the present study are consistent with these findings, indicating that similarity in hydrological regime is central to similarity in the composition of a zone's sciomyzid fauna.…”
Section: Discussionmentioning
confidence: 98%
“…This idea can be related to this study since all bog sites were completely surrounded by forested land before undergoing extreme anthropogenic transformations in the surrounding matrix. The IDH has explained diversity patterns for multiple wetland arthropod taxa (Ward and Stanford 1983;Townsend et al 1997;Whiles and Goldowitz 2001) and provides a possible explanation for the high diversity of assemblages from LAN and JON.…”
Section: Effect Of Vegetation Cover and Surrounding Land Usementioning
confidence: 97%